Mapping of 5q35 chromosomal rearrangements within a genomically unstable region. Issue 10 (15th July 2008) - Buysse, K; Crepel, A; Menten, B; Pattyn, F; Antonacci, F; Veltman, J A; Larsen, L A; Tümer, Z; de Klein, A; van de Laar, I; Devriendt, K; Mortier, G; et al.
Abstract : Background: Recent molecular studies of breakpoints of recurrent chromosome rearrangements revealed the role of genomic architecture in their formation. In particular, segmental duplications representing blocks of >1 kb with >90% sequence homology were shown to mediate non-allelic homologous recombination (NAHR). However, the occurrence of the majority of newly detected submicroscopic imbalances cannot be explained by the presence of segmental duplications. Therefore, further studies are needed to investigate whether architectural features other than segmental duplications mediate these rearrangements. Methods: We analysed a series of patients with breakpoints clustering within chromosome band 5q35. Using high density arrays and subsequent quantitative polymerase chain reaction (qPCR), we characterised the breakpoints of four interstitial deletions (including one associated with an unbalanced paracentric inversion), a duplication and a familial reciprocal t(5;18)(q35;q22) translocation. Results and conclusion: Five of the breakpoints were located within an interval of ∼265 kb encompassing the RANBP17 and TLX3 genes. This region is also targeted by the recurrent cryptic t(5;14)(q35;q32) translocation, which occurs in ∼20% of childhood T cell acute lymphoblastic leukaemia (T-ALL). In silico analysis indicated the architectural features most likely to contribute to the genomic instability of this region, which was supported by our molecular data. Of further interest, in two patients and the familial translocation, the delineated breakpoint regions encompassed highly homologous LINEs (long interspersed nuclear elements), suggesting that NAHR between these LINEs may have mediated these rearrangements.